Pengaruh Tarif Pajak Efektif, Mekanisme Bonus, Kontrak Utang, dan Penghindaran Pajak Terhadap Harga Transfer: Studi Empiris pada Perusahaan Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesi Tahun 2019-2023 - Riska Fatikasari; Cris Kuntadi; Rachmat Pramukty (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
The purpose of this study was to test and analyze the effect of effective tax rate, bonus mechanism, debt covenant, and tax avoidance on transfer pricing. This research method used quantitative research methods, with the types and sources of data used are secondary data obtained through the annual financial statements of companies listed on the Indonesian Stock Exchange. The population and samples in this study are the financial statements of basic industrial and chemical sector companies listed on the Indonesian Stock Exchange for the period 2019-2023. The sampling technique used was purposive sampling technique and resulted in a sample of 110 processed data samples that met the criteria. The analysis method used is descriptive statistical test, classical assumption test, multiple linear regression test, and hypothesis testing. The results of this study indicate that: (1) effective tax rate has no effect on transfer pricing; (2) bonus mechanism has a positive effect on transfer pricing; (3) debt covenant has a positive effect on transfer pricing; (4) tax avoidance has a positive effect on transfer pricing.